Knowledge and the Fall in American Neo-Calvinism: Toward a Van Til–Plantinga Synthesis - Békefi, Bálint (Philosophia reformata, 2022)
Cornelius Van Til and Alvin Plantinga represent two strands of American Protestant philosophical thought influenced by Dutch neo-Calvinism. This paper compares and synthetizes their models of knowledge in non-Christians given the noetic effects of sin and non-Christian worldview commitments. The paper argues that Van Til’s distinction between the partial realization of the antithesis in practice and its absolute nature in principle correlates with Plantinga’s insistence on prima facie–warranted common-sense beliefs and their ultimate defeasibility given certain metaphysical commitments. Van Til endorsed more radical claims than Plantinga on epistemic defeat in non-Christian worldviews, the status of the sensus divinitatis, and conceptual accuracy in knowledge of the world. Finally, an approach to the use of evidence in apologetics is developed based on the proposed synthesis. This approach seeks to make more room for evidence than is generally recognized in Van Tilianism, while remaining consistent with the founder’s principles.